The ticket chase. - Riebeek, H. (IEEE spectrum)
At a time when turbulence applies as much to an airline's financial status as to its flight status, cost is everything. Airlines recognize that the key to survival is cutting costs, and they are looking to technology to do just that. In particular, the airlines aim to slash a US 2.2 billion dollars item-a large part of the surprisingly expensive process of selling tickets, or distribution. To do so, they are counting on their own Web sites and other Internet based technology to link them directly to their customers at far lower cost.